The role of emotion regulation in improving the performance of futsal athletes - Hasna, Nuzulfa Maisya; Komarudin, Komarudin; Saputra, Mochamad Yamin; Novian, Geraldi (Jurnal Patriot, 2025)
Problems: Futsal athletes often have difficulty managing emotions when making mistakes, so athletes experience a decline in performance, such as being easily provoked by the audience, passing incorrectly, failing to shoot, and various other things. This makes it difficult for athletes to win matches and tend to blame each other. Purpose: This study aims to examine the role of emotion regulation in improving the performance of futsal athletes. Methods: Descriptive method with a quantitative approach was used involving this research which involved 10 UPI male futsal athletes. The instruments used in the study were Emotion Regulation Questionnaire (ERQ) and Game Performance Assessment Inventory (GPAI) which were given once to the sample. Pearson correlation test was used as the data analysis of this study. Results: The results showed that there is a significant relationship between emotional regulation and the performance of futsal athletes. Conclusion: This study concludes that emotion regulation has an important role in improving the performance of futsal athletes. It is important for coaches to be able to pay more attention to the emotional state of athletes in the athlete training process.